The refined Moho depth map in the Carpathian-Pannonian region - Miroslav BIELIK; Irina MAKARENKO; Kristián CSICSAY; Olga LEGOSTAEVA; Vitaly STAROSTENKO; Aleksandra SAVCHENKO; Barbora ŠIMONOVÁ; Jana DÉREROVÁ; Lucia FOJTÍKOVÁ; Roman PAŠTEKA; Jozef VOZÁR (Contributions to Geophysics and Geodesy, 2018)
We present a new digital Moho depth map of the Carpathian-Pannonian region. The map was produced by compiling Moho discontinuity depth data, which were obtained by interpretation of seismic measurements taking into account the results of 2-D and 3-D integrated geophysical modelling. The resultant map is characterized by significant Moho-depth variations. The trends and features of the Moho in this region were correlated with tectonic units.